2023
DOI: 10.13057/biodiv/d240174
|View full text |Cite
|
Sign up to set email alerts
|

Detection of multidrug-resistant (MDR) Staphylococcus aureus and coagulase-negative staphylococci (CoNS) in cow milk and hands of farmers in East Java, Indonesia

Abstract: Abstract. Khairullah AR, Kurniawan SC, Sudjarwo SA, Effendi MH, Afnani DA, Silaen OSM, Putra GDS, Riwu KHP, Widodo A, Ramandinianto SC. 2023. Detection of multidrug-resistant  Staphylococcus aureus and coagulase-negative staphylococci in cow milk and hands of farmers in East Java, Indonesia. Biodiversitas 24: 658-664. Cow milk is a nutrient-dense food containing various nutrients, i.e., carbohydrates, fat, and protein. However, it can potentially spread several pathogenic bacteria, such as staphylococci. Staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
1
1
Order By: Relevance
“…Khairullah et al [ 28 ] isolated 5.15% and 4.22% of MDR S. aureus and CoNS isolates from cow milk and farmers’ hands in East Java, Indonesia, which was significantly lower than the present study. Patterns in healthcare infrastructure, regulatory policies, socioeconomic conditions, climate, and geography all contribute to this change.…”
Section: Discussioncontrasting
confidence: 85%
“…Khairullah et al [ 28 ] isolated 5.15% and 4.22% of MDR S. aureus and CoNS isolates from cow milk and farmers’ hands in East Java, Indonesia, which was significantly lower than the present study. Patterns in healthcare infrastructure, regulatory policies, socioeconomic conditions, climate, and geography all contribute to this change.…”
Section: Discussioncontrasting
confidence: 85%
“…Sendang (a sub district in Tulungagung district) is one of a major milk-producing regions of East Java (Khairullah et al, 2023) revealed that breeders poor care practices for dairy cows with subclinical mastitis eventually progresses to clinical mastitis. There have been numerous reports of subclinical mastitis cases in Tulungagung district, which is consistent with the high volume of milk production and the presence of dairy cattle (Ramandinianto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%